High Wall Stress May Predict the Formation of Stent-Graft–Induced New Entries After Thoracic Endovascular Aortic Repair. (October 2018) - Menichini, Claudia; Pirola, Selene; Guo, Baolei; Fu, Weiguo; Dong, Zhihui; Xu, Xiao Yun
Purpose: To explore the potential role of morphological factors and wall stress in the formation of stent-graft–induced new entries (SINE) based on computed tomography (CT) images after thoracic endovascular aortic repair (TEVAR).Case Report: Two female patients aged 59 years (patient 1) and 44 years (patient 2) underwent TEVAR for type B dissection in the chronic (patient 1) or subacute (patient 2) phase. CT scans at 3-month follow-up showed varying degrees of false lumen thrombosis in both patients. At 14-month follow-up, a SINE was observed in patient 1 while the dissected aorta in the other patient remained stable. Morphological and finite element analyses were performed based on the first follow-up CT images. The computational results showed that the SINE patient had higher stent-graft tortuosity than the non-SINE patient and much higher wall stress in the region close to the distal SINE.Conclusion: This case study suggests that high stent-graft tortuosity can lead to high wall stress, which is potentially linked to the formation of SINE. Further large population-based studies are needed to confirm this preliminary finding.